Lima Pertimbangan Memilih Sekolah (Studi Kasus di SMA Muhammadiyah di Kabupaten Bantul) - Sahrul Akbar; Dian Hidayati (Journal of Education and Teaching (JET), 2023)
The impact of advances in technology and communication has almost changed all aspects of life, including the order of educational life, making parents more protective in choosing schools for their children. This makes parents tend to prefer religion-based schools with more religious lessons. This study aims to determine the factors that influence parents' decisions in choosing Muhammadiyah High School (SMA). The research method used in this study was quantitative involving 100 parents of students who chose Muhammadiyah schools in Bantul Regency. The results of this study found that parents chose Muhammadiyah schools because of location, distance, vision and mission factors, family support and religious learning. Parents choose Muhammadiyah schools in the hope of avoiding the negative impact of technological and communication advances because Muhammadiyah schools provide more religious learning.